Perception of Dental Professionals towards Biostatistics. (28th October 2014) - Batra, Manu; Gupta, Mudit; Dany, Subha Soumya; Rajput, Prashant
Abstract : Biostatistics is becoming an integral part of dental sciences. Awareness regarding the subject is not thoroughly assessed in the field of dentistry. So the study was conducted to assess dental professionals' knowledge, attitude, and perception toward biostatistics at an academic dental institution. An anonymous cross-sectional questionnaire survey was conducted among all the faculty and postgraduate students of two dental colleges in Moradabad, Uttar Pradesh. The responses were assessed on 5-point likert scale. The survey response rate was 73.71%. Two-thirds of respondents believed biostatistics to be a difficult subject and at the same time half of them did not consider it to be more difficult than other subjects in dentistry. Females were less competent than males in applying biostatistical skills which was found to be statistically significant. Results suggested that dentists with research or academics as an adjunct to their clinical practice had better command over the subject. The current study shows that there is lack of command over the subject of biostatistics among dental professionals although they were aware of its importance in dentistry. There is a need of changing the training pattern of biostatistics for dental professionals which would make them confident enough to apply biostatistics in their clinical practice.